2006
DOI: 10.1103/physrevb.73.085318
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and thermal dependence of phase coherent photorefractivity in ZnSe quantum wells

Abstract: We investigate the spectral and thermal dependence of an exciton resonant all-optical and phase coherent photorefractive effect in a ZnSe single quantum well by four-wave mixing using 90 fs pulses. The observed phase coherence is attributed to an exciton-induced formation of an electron grating within the quantum well. The diffracted signal exhibits an exponential decay that is equal to the exciton dephasing rate and it shows a pronounced suppression at the temporal overlap of incident pulses. With decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous investigations 12,13 also revealed that the decay time of the exciton induced electron grating in the PCP QW is in the ϳ10 s range. 12 and 13͒ using ultrashort light pulses at a temperature of ϳ50 K. Compared to current PR QW devices these all-optical PCP QWs operate without electrical contacts at a spectral efficiency of Ϸ 5 ϫ 10 −4 .…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Previous investigations 12,13 also revealed that the decay time of the exciton induced electron grating in the PCP QW is in the ϳ10 s range. 12 and 13͒ using ultrashort light pulses at a temperature of ϳ50 K. Compared to current PR QW devices these all-optical PCP QWs operate without electrical contacts at a spectral efficiency of Ϸ 5 ϫ 10 −4 .…”
mentioning
confidence: 86%
“…The maximum frame rate is limited by the decay time of the electron grating in the PCP QW, which is in the ϳ10 s range. 12,13 Within an accuracy of Ϯ10 m, we determine a step height of ϳ65 m, which is somewhat less than the 80 m obtained from the micrograph. However, due to the coherence of excitons, the entire depth profile of a reflecting object is encoded by its brightness in the holographic image.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we discovered an all-optical phasecoherent photorefractive (PCP) effect in a ZnSe single quantum well (QW) grown on (001) GaAs using ultrashort light pulses in a two-beam four-wavemixing (FWM) configuration [1,2]. The exciton resonant light pulses create both a coherent exciton polarization in the QW and highly excited electronhole (e-h) pairs in the GaAs substrate.…”
Section: Introductionmentioning
confidence: 99%